SOSIALISASI PEMANFAATAN HERBAL DRINK DAUN SALAM SEBAGAI PENGOBATAN TRADISIONAL - Ni Made Sukma Sanjiwani; I Wayan Sudiarsa (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
On the activities of dedication is followed by 82 people whose goal is a student program DIII and S1 Pharmacy Faculty of Pharmacy University of Mahasaraswati Denpasar. Devotion is preceded by the provision of a list of present and pre-test further provision of material and lectures, giving the video and discussion and closed with the provision of post-test. Socialization use of herbal drink leaves regards as treatment traditionally in order to treat pressure blood high and increase the interest of students that want to create and consume herbal drink is independent. Devotion is done with the purpose to provide knowledge to the students that leaves greeting is a drug traditionally that can be made in the from of dosage pharmaceutical from of drinks herbs is useful for treating acid uric and pressure blood high as in the leaves of a greeting is no womb chemistry. The content of the chemical leaves and bruk trunks greeting many containing oil volatile, tannins, saponins and flavonoids, in addition to the leaves alkaloids and polyphenols . In addition , the active compounds in bay leaf ß-sitosterol and niacin.